Potential impacts of Covid-19 on autoimmune diseases: a case report on Systemic Sclerosis - Mahayidin, Hasni; Jamalut, Yusanita; Zaini, Adilahtul Bushro (Universiti Putra Malaysia, 2024)
Systemic sclerosis (SSc) is a rare autoimmune disease characterised by fibrosis of the skin, musculoskeletal system and internal organs, with clinical presentations ranging from rapidly progressive to chronic forms. The Covid-19 pandemic has highlighted potential links between infections and autoimmune diseases. We report a 49-year-old female with a history of Covid-19 reinfection who presented with long Covid symptoms. She was discovered to have a five-year history of multiple joint pain and recently developed bilateral swollen fingers with distal skin thickening extending to the elbows. Investigations revealed strong ANA and anti-Scl-70 positivity while CT thorax showed features of autoimmune interstitial lung disease. She was diagnosed to have long Covid with limited cutaneous SSc. Although the link between Covid-19 and SSc remains unclear, this case underscores the potential impacts of Covid-19 on pre-existing autoimmune diseases, including acceleration of disease progression, overlapping of symptoms and increased diagnostic rates due to heightened health awareness.